Occurance of fall armyworm, Spodoptera frugiperda on maize (Zea mays) in higher altitudes of Kashmir, India: First report - AHAD, ISHTIYAQ; ARSHIMA SHAJI V; AZIZ, DANISHTA; PANDA, ARADHANA; SHAH, ISHFAQ MAJEED; KHAN, ZAKIRH; T, VENKATESAN; D R, BAJYA (The Indian Journal of Agricultural Sciences, 2025)
Maize queen of cereals is almost grown in every part of India, particularly under hilly areas as a mixed crop. However, this crop is prone to damage from various insect pests and diseases due to frequently changing weather conditions. One such invasion of an insect pest in India which within a year of invasion, made its way throughout maize-growing regions of India, endangering the maize crop growing area is the fall armyworm. The first occurrence of fall armyworm, in the western Himalayan region, with similar nature of infestation was noticed during 2022–23 in the maize fields of Sher-e-Kashmir University of Agricultural Sciences and Technology, Wadura, Sopore, Jammu and Kashmir. Both early and late instar larvae were found to form holes in maize plants, eating on the edges of the leaves with newly excreted debris suggesting their establishment on their host. During the investigation at morphological level, it was seen that the pest under study was fall armyworm. Later on the molecular characterization of this pest, done at ICAR-National Bureau of Agricultural Insect Resources, Bengaluru, Karnataka also confirmed it. The query sequences were showing much resemblance with the sequences retrieved from GenBank, MW561302, MW561305, MW561310, MW561313, OQ920981, MT180097 and OQ150895 and was sharing a common intra-specific distance of 0.00153% with all the sequences. Hence, morphomolecular characterization of this pest confirmed the first report of the occurrence of fall armyworm in maize crops of Kashmir region of Jammu and Kashmir, India.